The spike state in type-I mesoscopic superconductor - de Oliveira, Isaias G. (2021)
We study here the spike state found in mesoscopic type I superconductors whose existence is confined to the single field where the superconducting state arises from the normal state in descending field in the so-called genuine type I regime. The mesoscopic type I superconductor possesses distinct κ regimes due to its richer critical field structure Cadorim et al. (2021) [11]. The lifetime of the spike state is shown to be in the nanosecond scale through the time dependent Ginzburg-Landau (TDGL) equations. The spike state is a giant vortex state that undergoes a process of deformation after its creation when several bubbles of vortices are expelled forming new but deformed giant vortices until no one is left inside the superconductor. Like phase slips and kinematic vortices, the spike state is also a non-equilibrium vortex state.